Association between prevalence and severity of chronic kidney disease and employment status: a nationwide study in Korea - Seoyeong Choi; Suk-Yong Jang; Eunjeong Choi; Yu shin Park (BMC, 2024)
Abstract Background The prevalence of chronic kidney disease (CKD) is increasing globally, and understanding the association between CKD and employment status is crucial. This cross-sectional study aimed to investigate the association of CKD with employment and occupation type among patients with CKD. Methods We analyzed data from 36,732 Korean adults aged ≥ 30 years, who participated in the Korean National Health and Nutrition Examination Survey between 2014 and 2021. CKD was detected based on the estimated glomerular filtration rate, and the employment status of the participants was classified into distinct categories: full-time permanent employment, unemployment, self-employment, and precarious employment. We analyzed the data using multiple logistic regression. Results We observed a significant association between CKD and a higher likelihood of unemployment compared to that in individuals without CKD (odds ratio, 1.70; 95% confidence interval, 1.47-1.96). This association was more prominent in patients with severe CKD. In the multivariable logistic analysis, patients with CKD had a higher likelihood for precarious employment (odds ratio, 1.29; 95% confidence interval, 0.92-1.88), self-employment (odds ratio, 1.3; 95% confidence interval, 0.90-1.88), and unemployment (odds ratio, 2.10; 95% confidence interval, 1.51-2.92) compared to individuals without CKD. Conclusions Our study demonstrated that CKD is associated with a higher likelihood of unemployment and engagement in precarious employment. These findings highlight the challenges faced by patients with CKD in obtaining stable employment and emphasize the need for interventions to improve the employment outcomes of individuals with CKD.